Surface air temperature - J. Overland; Edward Hanna; I. Hanssen-Bauer; S.-J. Kim; J. E. Walsh; M. Wang; U. S. Bhatt; R. L. Thoman (2015)
•Average annual surface air temperature anomaly (+1.3°C) over land north of 60°N for October 2014-September 2015 was the highest in the observational record beginning in 1900; this represents a 2.9°C increase since the beginning of the 20th Century.•Average air temperature anomalies in all seasons between October 2014 and September 2015 were generally positive throughout the Arctic, with extensive regions exceeding +3°C relative to a 1981-2010 baseline.•Anomalously warm conditions from November 2014 through June 2015 in Alaska were caused by weather patterns that advected warm mid-latitude air northward from the northeast Pacific Ocean. Anomalously warm Arctic conditions during spring (April, May, June) 2015 across central Eurasia were also due to southerly winds.•Strong connections between the Arctic and the mid-latitudes were also seen in late winter-early spring (February-April) 2015, when cold air advected south-eastward from the central Arctic resulted in major negative temperature anomalies over eastern North America.